THE NEED OF TEACHING MATERIALS BASED ON PROBLEM BASED LEARNING TO IMPROVE STUDENTS’ LEARNING OUTCOMES AT ELEMENTARY SCHOOLS - Dian Ferdiana; Irfai Fathurohman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aimed to describe the needs of teaching materials based on Problem Based Learning, especially at grade VI SD Negeri Sukoharjo 01. The expected result was to support the design of teaching materials in order to improve students’ learning outcomes. This research was a research and development that implemented ten steps including potentials and problems, data collections, product designs, design validations, design revisions, product testings, product revisions, trial uses, product revisions, and dissemination. The needs of teaching material were analyzed based on teachers’ and students’ perceptions which was conducted on 50 students at grade 6 in the experimental class, and 40 students in the control class. The data were collected through a questionnaire for teaching material needs and a test of students’ learning outcomes. Based on the teachers’ and students’ perceptions, there were four aspects found in this research: (1) book content (88.5%), (2) language (92.25%), (3) presentation (96.25%), and (4) graphics (94.4%). Gain test indicated an increase on students’ learning outcomes for as much as 0.49 with moderate criteria from the affective, cognitive, and psychomotor aspects. Then, t-test resulted 12.836> 0.05 which meant that the hypothesis H1 was accepted. There was a difference on the learning outcomes between the experimental class and the control class. From the results of this study, it can be concluded that based on the needs analysis, materials based on problem-based learning can improve students’ learning outcomes.